(untitled) (Modern information system and technologies, 2018)
The article deals with theoretical information about the system of residual classes (SRC). The principles of information processing in the SRC are formulated. The study of the influence of the main properties of SRC on the architecture and the principles of the functioning of a specialized computing device (SCD) was carried out. The structure of the SCD in the SRC has been developed and studied. The mathematical model of reliability of SCD in the SRC is developed. A comparative analysis of the reliability of SCD in the SRC was conducted. Keywords: automated control system, electronic computing machine, system of residual classes, specialized computing device, positional numerical system.